2011
DOI: 10.1186/1471-2458-11-839
|View full text |Cite
|
Sign up to set email alerts
|

Good places for ageing in place: development of objective built environment measures for investigating links with older people's wellbeing

Abstract: BackgroundThere is renewed interest in the role of the built environment in public health. Relatively little research to date investigates its impact on healthy ageing. Ageing in place has been adopted as a key strategy for coping with the challenges of longevity. What is needed is a better understanding of how individual characteristics of older people's residential environments (from front door to wider neighbourhood) contribute to their wellbeing, in order to provide the basis for evidence-based housing/urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 52 publications
1
75
1
6
Order By: Relevance
“…Older adults with declining health and functional status can be particularly limited in their mobility by barriers in their local area (Burton, Mitchell, & Stride, 2011). Previous studies have shown that the physical environment can have an impact on the independence and quality of life of older people living in the community (Burton et al, 2011;Lui, Everingham, Warburton, Cuthill, & Bartlett, 2009;Gilroy, 2008).…”
Section: Accessibility Of the Local Areamentioning
confidence: 99%
“…Older adults with declining health and functional status can be particularly limited in their mobility by barriers in their local area (Burton, Mitchell, & Stride, 2011). Previous studies have shown that the physical environment can have an impact on the independence and quality of life of older people living in the community (Burton et al, 2011;Lui, Everingham, Warburton, Cuthill, & Bartlett, 2009;Gilroy, 2008).…”
Section: Accessibility Of the Local Areamentioning
confidence: 99%
“…Of particular relevance is its role in addressing the challenges of an ageing society (Burton et al, 2011), a worldwide phenomenon. To reduce the burden of care, policies now centre on facilitating independence in older age or allowing people to 'age in place'.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research in the area of the impact of built environment on health has concentrated on the links between neighbourhood characteristics and physical activity or obesity [8][9][10][11]. It is important to investigate the role of the built environment particularly in ageing population.…”
Section: Introductionmentioning
confidence: 99%
“…Older people spend more time in their home and community environments, barriers in environment can make more difficult dealing with declining health and functional status [8,12]. Recent studies have suggested that wellbeing in later life is closely related to the physical environment [8,13], and in specific, parks and walking areas, adequate parking facilities for persons with disabilities, and public transportation have been associated with functioning and disability in older adults [14] The ability of older people to function and remain active in their setting of choice and to continue to enjoy their desired level of support and interaction with other people are the main indicators that an environment is positive [15]. The physical characteristics of the built environment influence significantly mobility, independence and quality of life of ageing population living in a local community [16].…”
Section: Introductionmentioning
confidence: 99%